Conflict Resolution of the 288 Movement in Indonesia: Searching for Causes, and Actors - Alam, Jundan Restu; Aditya, Rahman; Yudho P, Lukman; Azhari, Yulian (International Journal of Education, Vocational and Social Science, 2026)
This study examines the 288 Action Movement in Indonesia, tracing the roots of the conflict, actors, and objectives through digital-based qualitative methods and NVivo analysis. The conflict was triggered by the issue of salary increases for members of the House of Representatives, which sparked widespread demands and revolutionary narratives. Key actors included civil society (citizen actions), students, workers, and those calling for action. The analysis shows an imbalance between legal guarantees and security practices, where public criticism is often considered a threat. Using Galtung's framework, the conflict resolution model identifies the dominance of Negative Peace (N), which focuses only on the elimination of direct violence. The model concludes that the government has not fully implemented Positive Peace (P)—the elimination of Structural Violence—a condition that risks repeating the events of the 1998 Reformation. The results recommend the need for a more dialogical and sustainable resolution model.